A fluorogenic substrate for the detection of lipid amidases in intact cells - Mireia Casasampere; Johnson Ung; Alejandro Iñáñez; Carine Dufau; Kazuhito Tsuboi; Josefina Casas; Su-Fern Tan; David J. Feith; Nathalie Andrieu-Abadie; Bruno Segui; Thomas P. Loughran, Jr.; José Luis Abad; et al. (Journal of Lipid Research, 2024)
Lipid amidases of therapeutic relevance include acid ceramidase (AC), N-acylethanolamine-hydrolyzing acid amidase, and fatty acid amide hydrolase (FAAH). Although fluorogenic substrates have been developed for the three enzymes and high-throughput methods for screening have been reported, a platform for the specific detection of these enzyme activities in intact cells is lacking. In this article, we report on the coumarinic 1-deoxydihydroceramide RBM1-151, a 1-deoxy derivative and vinilog of RBM14-C12, as a novel substrate of amidases. This compound is hydrolyzed by AC (appKm = 7.0 μM; appVmax = 99.3 nM/min), N-acylethanolamine-hydrolyzing acid amidase (appKm = 0.73 μM; appVmax = 0.24 nM/min), and FAAH (appKm = 3.6 μM; appVmax = 7.6 nM/min) but not by other ceramidases. We provide proof of concept that the use of RBM1-151 in combination with reported irreversible inhibitors of AC and FAAH allows the determination in parallel of the three amidase activities in single experiments in intact cells.